2013
DOI: 10.1063/1.4817378
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the charge surface distribution on the flow field induced by a dielectric barrier discharge actuator

Abstract: The Electro-Hydro-Dynamics (EHD) interaction induced by a surface dielectric barrier discharge in the aerodynamic boundary layer at one atmosphere still air has been investigated. Three different geometrical configurations of the actuator have been utilized. In the first configuration, an electrode pair separated by a 2 mm dielectric sheet has been used. The second and the third configurations have been obtained by adding a third electrode on the upper side of the dielectric surface. This electrode has been pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…4) and electrode diameters in the circular case (D in Fig. 4) of 10,14,18,22,26,30,34,38,42,46, and 50 mm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…4) and electrode diameters in the circular case (D in Fig. 4) of 10,14,18,22,26,30,34,38,42,46, and 50 mm.…”
Section: Methodsmentioning
confidence: 99%
“…This ionic wind can significantly modify the properties of the boundary layer developing on body surfaces [3]. Interest for this phenomenon is growing in aeronautics, astronautics [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], and for turbine blade applications [21][22][23][24][25]. Plasma aerodynamic actuators are more attractive than other active actuator technologies because they feature high dynamic responses due to the absence of moving parts and low weight, they are easy to build, backward compatible with existing aerodynamic surfaces, and generate negligible aerodynamics interferences when not in use.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22] The appearance of surface potential far from the discharge plasma regime is probably formed by the surface migration of the accumulated charges. 20,24,25 The axial surface potential distributions, with the V pp ¼ 12 kV AC voltage superimposed on the DC bias of þ1 kV, þ3 kV, þ5 kV, þ7 kV and À1 kV, À3 kV, À5 kV, À7 kV, are shown in Fig. 9.…”
Section: A Surface Potential Distributionmentioning
confidence: 99%
“…The result showed that the surface potential depended primarily on the bias voltage. Cristofolini et al 24,25 also measured the surface potential distribution for different discharge periods and different dielectric materials. However, the effects of plasma actuators with different air-exposed electrodes on the surface potential distribution and surface potential (especially after a) rchsh@dlut.edu.cn 1070-664X/2015/22(4)/043518/8/$30.00 V C 2015 AIP Publishing LLC 22, 043518-1 adding bias voltage) on the airflow field have not yet been studied carefully.…”
Section: Introductionmentioning
confidence: 98%
“…Thus, the surface potential is formed. The appearance of surface potential in the far downstream of the plasma regime can be attributed to the migration of the accumulated charges along the quartz glass plate surface [37], [38].…”
Section: ) Surface Potential Distributionmentioning
confidence: 99%